Influences of Salinity on Embryonic and Larval Development of Striped Catfish Pangasianodon hypophthalmus - Hossain, Farzana; Islam, S. M. Majharul; Ashaf-Ud-Doulah, Mohammad; Ali, Md Shaha; Islam, Md Sadiqul; Brown, Christopher; Shahjahan, Md (Frontiers in Marine Science, 2021)
Salinity intrusion in coastal areas due to climate change is alarming. In this study, the effects of salinity on embryonic and larval development of striped catfish (Pangasianodon hypophthalmus) were studied experimentally. Embryos and larvae were exposed to seven salinity treatments (0, 2, 4, 6, 8, 10, and 12 ppt), each with three replications. Considerable survivability of embryos was recorded up to 6 ppt salinity. Mortality of embryos significantly increased at 8 and 10 ppt salinity, and 100% mortality was displayed within 12 h of exposure at 12 ppt salinity. The rate of hatching was significantly reduced at 8 and 10 ppt salinity. The 24 h lethal concentration (LC50) value of salinity for embryo was 11.24 ppt. Different types of deformities, such as undeveloped yolk sac, elongated gastrula yolk sac, and yolk sac bud, were highest at 10 ppt salinity. Similar to the embryo, considerable survivability of larvae was recorded up to 6 ppt salinity, and 100% mortalities were found within 24 h of exposure at 12 ppt salinity. The 24 and 48 h LC50 values of salinity for larvae were 10.63 and 8.48 ppt, respectively. Several types of deformities, including yolk sac ulceration, spine scoliosis, tail bent, yolk sac edema, and compromised swim bladder inflation, were highest at 10 ppt salinity after 48 h of exposure. Within 24 h of exposure, about 80% yolk sac of the larvae was absorbed at 8 and 10 ppt salinity, while 30%–50% yolk sac was absorbed at 0–6 ppt salinity. Growth rates in terms of length and weight were higher at 0, 2, and 4 ppt salinity and moderate at 6 and 8 ppt salinity. Overall, the current findings define the limits to optimize hatchery procedures for the culture of this species in low saline brackish water.